The efect of commercial functional food with probiotics on microorganisms from early carious lesions (2020)
Caries rates in school-age children are still high enough to be the cause of serious concern for health systems in diferent countries. The biotechnology strategies studied to decrease these rates include the consumption of probiotics—available via a variety of functional foods obtainable on the market— that are able to inhibit bacteria associated with this disease. In this vein, the purpose of this study was to determine the efect of these foods on the growth of microorganisms in early carious lesions in children aged between 6 and 12. In the frst phase, an agar well difusion method was applied to selected foods, available in supermarkets, which contain probiotics that have already been shown to inhibit Streptococcus mutans (ATCC 25175), and to lower the pH in liquid culture media. In a second phase, these foods (n= 4) were examined in terms of their ability to inhibit the microorganisms in contact with early carious lesions in children and to reduce the pH of mixed cultures combined with the food. The results revealed that, of the foods tested, three inhibit the growth of microorganisms in carious lesions and, at the same time, lower the pH of the culture by more than 2.5 units. The food with the highest inhibitory capacity (14 mm, IQR 13–14) showed a similar efect among patients (P> 0.05), which together with the fact that its sugar concentration is less than 10%, makes it an ideal candidate for clinical study.